Developing Community-Based Interventions to Promote Healthy Breakfast Culture - Fitri Nur Fadhillah (Eduvest - Journal of Universal Studies, 2024)
Breakfast is an important part of a healthy lifestyle. However, there are still many individuals who skip breakfast or do not have a healthy breakfast culture. This habit can have a negative impact on long-term health, especially in children and teenagers who are still growing. The aim of this research is to develop a community-based intervention that is effective in increasing the culture of healthy breakfast among the community. This research uses a qualitative approach. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that intervention by effective community-based health promotion workers can increase the culture of healthy breakfasts. Implementation of this intervention development can be done in various ways, including education about the importance of a healthy breakfast, demonstrations on how to make a healthy breakfast, training of health cadres to become educational agents and motivators for the community, collaboration with schools and workplaces to provide healthy breakfast foods, promotion of healthy breakfasts. through social media and communities.